Web-Based Digital Marketing Application for Selling Qurban Animals in Qurban Cages in Sidoarjo Regency - Silvie Nur Millah; Arif Senja Fitrani (Universitas Muhammadiyah Sidoarjo, 2022)
Technological advances in various fields of technology encourage the emergence of various new innovations that have a very positive impact on the world of trade. With the number of internet users increasing day by day, it opens up opportunities for entrepreneurs to develop their business through mobile phones. Like cattle and goats, which are in great demand by the public for religious purposes or for consumption, the demand for these animals increases at the time of Eid al-Adha. In 2019, beef consumption was 18,913,246 tons while goat meat was 8,608,121 tons. However, in buying and selling activities, cattle farmers still use simple information media so that they are not optimal. Therefore, to support the sales process, a web-based information system is needed. Customers will find it easier to access the information they need at any time regarding prices, conditions, and maintenance. This application is made using the waterfall method starting from analysis, design, coding, testing, to maintenance. With these problems, the authors examine the existing problems, namely